2016
DOI: 10.1016/j.molcel.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Efflux Activity Facilitates Drug Tolerance in Dormant Bacterial Cells

Abstract: SummaryNatural variations in gene expression provide a mechanism for multiple phenotypes to arise in an isogenic bacterial population. In particular, a sub-group termed persisters show high tolerance to antibiotics. Previously, their formation has been attributed to cell dormancy. Here we demonstrate that bacterial persisters, under β-lactam antibiotic treatment, show less cytoplasmic drug accumulation as a result of enhanced efflux activity. Consistently, a number of multi-drug efflux genes, particularly the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
318
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(342 citation statements)
references
References 48 publications
16
318
2
6
Order By: Relevance
“…This is also very well established [e.g., Ref. (139, 190203)]. In many cases, they can hide intracellularly (204), where antibiotics often penetrate poorly (205) because the necessary transporters (206209) are absent.…”
Section: Prevalence Of Dormant Persistent or Latent Bacteria In Infmentioning
confidence: 79%
“…This is also very well established [e.g., Ref. (139, 190203)]. In many cases, they can hide intracellularly (204), where antibiotics often penetrate poorly (205) because the necessary transporters (206209) are absent.…”
Section: Prevalence Of Dormant Persistent or Latent Bacteria In Infmentioning
confidence: 79%
“…Antibiotic treatment and environmental stresses can give rise to population heterogeneity and confer phenotypic protection against lethality [81]; simple examples include variable expression of multi-drug efflux pumps [82] and stochastic formation of persister cells by toxin-antitoxin systems and the ppGpp-mediated stringent response [83,84]. Recent studies have revealed several additional persister mechanisms, including ATP depletion [85,86], morphological differentiation [87], inter-cell signaling [88,89], and toxin-antitoxin-mediated inhibition of proton-motive force [90,91] or protein translation [92].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…La lenta eliminación de esta sub-población de bacterias persistentes puede ser explicada porque la actividad de CFX se redujo a causa de la disminuida respiración celular (Lobritz et al, 2015) y la mayor actividad de las bombas de eflujo de este tipo de bacterias (Pu et al, 2016). La presencia de una subpoblación de bacterias persistentes determinó que la erradicación de E. coli 09-684 pasara a depender del tiempo de exposición a CFX.…”
Section: Modo De Acción De Cfx Sobre E Coli 09-684unclassified